Gastro-Colo-Cutaneous Fistula Occurring After Percutaneous Endoscopic Gastrostomy Procedure - Juyung Joung; Jeeyeon Baek; Sun Hyung Kang; Hee Seok Moon; Jae Kyu Sung; Hwan Jung Yun (Yong Chan Lee, 2024)
An 82-year-old man diagnosed with supraglottic cancer sought a consultation for percutaneous endoscopic gastrostomy (PEG) placement. Preoperative chest radiography (posterior-anterior [PA] view) revealed no abnormalities, and PEG tube placement was performed using the "pull" method. Chest radiography (PA view) performed 3 days postoperatively showed free air that was not observed immediately after PEG tube placement; therefore, the patient was diagnosed with pneumoperitoneum. Abdominal computed tomography confirmed that the PEG tube was appropriately positioned within the stomach; however, the colon was observed between the abdominal wall and stomach, which indicated that the PEG tube had passed through the colon. Review of preoperative chest radiographs (PA views) confirmed that the colon was visualized in the area wherein usually stomach gas should have been observed. The patient was diagnosed with a gastro-colo-cutaneous fistula that occurred postoperatively, following a procedure that was performed without confirmation of anatomical variations. The PEG tube was removed surgically, and we performed percutaneous gastrostomy.